Beyond ivy walls [large type] - Fordham, Rachel, 1984- (Center Point Large Print, 2024)
"Reminiscent of Beauty and the Beast, a recluse and a young woman discover that the scars of life are no match against an act of love. Iowa, 1903. All of Monticello believes Otis Taylor has been away fostering his musical genius. But the truth is that his father exiled him long ago, rejecting Otis's appearance and the scars that came with it. Now that he is the last living Taylor, Otis has covertly returned to settle his family's affairs and rid himself of his past for good. However, he soon discovers that he may not have been the only discarded Taylor and begins a tireless search for his missing niece. At twenty-three years old, Sadie West left her family farm and found employment at the Hoag feather duster factory. It isn't a romantic job, but she's hardly had a glimmer of romance since her beau went off to college, leaving her with no promise of a future together. Desperate to save money and help her family make ends meet, she trespasses and finds shelter in an abandoned building -- and is thrown in the path of the town's mysterious bachelor. Otis's wounds are deep, but as Sadie's friendship with him grows, she begins to fall for the man beneath the mask. The mystery of his long-lost niece, however, is more complex than either could have imagined, and Sadie may be the key to Otis Taylor finally finding his way home."--